2009
DOI: 10.1590/s0073-47212009000100017
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio and morphological characteristics of rufous gnateaters, Conopophaga lineata (Aves, Passeriformes) in Atlantic forest fragments

Abstract: ABSTRACT. Unequal sex ratios lead to the loss of genetic variability, decreasing the viability of populations in the long term. Anthropogenic activities often disturb the natural habitats and can cause alterations in sex ratio and morphological characteristics of several species. Forest fragmentation is a major conservation concern, so that understanding its effects in natural populations is essential. In this study, we evaluated the sex ratio and the morphological characteristics of Rufous Gnateaters (Conopop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Small sample sizes and studies conducted solely in small forest fragments or human-modified environments can bias reproductive success (Oniki 1979, Martin 1996. At least C. lineata appears to respond well to forest fragmentation, surviving in small fragments without significant changes in sex ratio (Dantas et al 2009) or nesting capacity (Marini et al 2007) despite morphological alterations being reported (Anciães & Marini 2000, Dantas et al 2009. However, in a small forest fragment, Willis et al (1983) found three infertile eggs in two of four monitored nests of the species; inbreeding and insecticides used in nearby crop fields were hypothesised as possible causes.…”
Section: Discussionmentioning
confidence: 99%
“…Small sample sizes and studies conducted solely in small forest fragments or human-modified environments can bias reproductive success (Oniki 1979, Martin 1996. At least C. lineata appears to respond well to forest fragmentation, surviving in small fragments without significant changes in sex ratio (Dantas et al 2009) or nesting capacity (Marini et al 2007) despite morphological alterations being reported (Anciães & Marini 2000, Dantas et al 2009. However, in a small forest fragment, Willis et al (1983) found three infertile eggs in two of four monitored nests of the species; inbreeding and insecticides used in nearby crop fields were hypothesised as possible causes.…”
Section: Discussionmentioning
confidence: 99%
“…Small sample sizes and studies conducted solely in small forest fragments or human-modified environments can bias reproductive success (Oniki 1979, Martin 1996). At least C. lineata appears to respond well to forest fragmentation, surviving in small fragments without significant changes in sex ratio (Dantas et al . 2009) or nesting capacity (Marini et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, indirect evidence for such association stems from a series of studies on a small understory passerine bird of fragmented Brazilian Atlantic rainforest. Rufous gnateaters ( Conopophaga lineata ) that were captured in tiny rainforest fragments showed both larger [30] and more asymmetric [1] wings compared to conspecifics captured in larger forests, and the shift in trait size was interpreted as an adaptation to disperse among poorly-connected forest fragments [30]. While the underlying developmental mechanism(s) remain to be tested in our study (as is the case for most processes related to FA; [6]), the fact that enlarged traits showed higher levels of FA than traits that decreased in size, suggests that high growth rates may have compromised mechanisms controlling early trait development [33], [34].…”
Section: Discussionmentioning
confidence: 99%
“…98% over the last 200 years, as a result of agricultural expansion, logging, pole cutting and cattle grazing, and formerly continuous tracts of rainforest became subdivided in small, isolated fragments, most strongly so since the early 1960s [25]–[27]. Based on 18 years of demographic, genetic and dispersal data from eight forest-restricted bird species [28], [29], it was earlier shown that this decrease in landscape connectivity resulted in a significantly loss in mobility over time in some species, while others seemed to cope better, possibly as a result of phenotypic and/or behavioural adaptations ([28]; see also [30], [31]). In addition to landscape-level effects on mobility, species also varied in their sensitivity to patch-level forest degradation, as inferred from historic changes in tarsus FA between museum specimens (collected prior to degradation) and post-degradation live captures from the same localities [32].…”
Section: Introductionmentioning
confidence: 99%